Willing to Think Hard? The Subjective Value of Cognitive Effort in Children. Issue 4 (11th April 2017) - Chevalier, Nicolas
Abstract : Cognitive effort is costly and this cost likely influences the activities in which children engage. Yet, little is known about how school‐age children perceive cognitive effort. The subjective value of cognitive effort, that is, how valuable or costly effort is perceived, was investigated in seventy‐three 7‐ to 12‐year‐olds using an effort discounting paradigm. In two studies, it varied with task difficulty but not age, was predicted by actual effort engagement but not actual success and related to trait interest in effortful activities and proactive control engagement. Children are sensitive to cognitive effort and use it to guide behaviors, suggesting that poor performance may often reflect reluctance to engage cognitive effort rather than low ability.